Ask a Question
x

Choose Country Code

x

Direction

x

Ask a Question

  • Ask a Question
  • Scan a Question
  • Post MCQ
  • Note: File extension must be of jpg, jpeg, png, bmp format and file size must not exceed 5 MB
x

Ask a Question

x

Hire a Tutor

Answers and Solutions

What's Your Question?
Answer
3px-py+3qx-qy =p(3x-y)+q(3x-y)=(3x-y)(p+q)
Answer

Answer:   An equation should have  one LHS and one RHS with an equal sign between them.

If the eqauality sign doesnt exist, then it is not an equation ,but only an expression.An expression could only be simplified and cannot be solved as there is nothing to solve. The present question is only an expression and so cannot be solved.The students should clearly understand the difference between expression and equation.

Answer
Its not an equation but an expression. See attachment
Answer
3px-py+3qx-qy Take 3x common from 1st and 3rd term 3x(p+y)-py-qy Now take -y common 3x(p+q)-y(p+q) Now take p+q common (p+q)(3x-y)
Answer

3px-py+3qx-qy

=p(3x-y)+q(3x-y)

=(p+q)(3x-y)

Answer

=3px-py+3qx-qy

=3x(p+q)-y(p+q)

=(p+q)(3x-y)

Answer
3px-py+3qx-qy=3px+3qx-py-qy=3x(p+q)-y(p+q)=(p+q)(3x-y)
Answer

3px - py + 3qx - qy

= p (3x-y) + q (3x-y)

= (3x-y) (p+q)

Post Answer and Earn Credit Points

Get 5 credit points for each correct answer. The best one gets 25 in all.

Post Answer